Multipurpose City Data Bank and its application in Pavement Management System - Ambrusné Somogyi, Kornélia (Acta Agraria Kaposváriensis, 2006)
A Multipurpose Data Bank has been developed. This contains the most important data of a city, which are related to the traffic system: road sections, bridges, junctions, traffic lights and sings, pedestrian and bike traffic size, etc. The system contains the coordinates of junctions, the traffic data, the recent and future conditions of the elements. This system could be used by the PMS, traffic management, traffic assignment and forecasting and other management, maintenance and rehabilitation systems. A IVth generation software a relation data base system is used. The connected OLE objects (pictures, movies) help the visualization of the elements. After the review of database, coming the exposition of the pavement management system.
Keywords: database; pavement management system; optimization